2017
DOI: 10.19044/esj.2017.v13n27p19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Growth Hormone replacement therapy on Lipid Metabolism in Georgian patients with Growth Hormone Deficiency

Abstract: Introduction: Recently, Growth hormone deficiency (GHD) has become one of the reasons of significant metabolic and psychological morbidity in children and adults. The aim of our study was to find out the impact of GH replacement therapy on lipid profile in Georgian patients with GHD, which was caused by surgical resection. Design: Double Blind placebo controlled study for 12 months and an open study for another 12 months. Patients and Methods: 20 Georgian adults, aged 40.75±2.2 years (mean ± SE, range 20.5-60)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In recent years, research on atherosclerotic disease has focused mainly on changes in the lipid profile, since large studies have shown a correlation between dyslipidemia and coronary artery disease. 4,5 The Framingham study, conducted with about 5,000 residents of this community in Massachusetts, showed a increased risk of higher levels of LDL cholesterol and lower HDL. Once this correlation has been demonstrated, several studies have succeeded, confirming the hypothesis that it is possible to control cardiovascular events by normalizing cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on atherosclerotic disease has focused mainly on changes in the lipid profile, since large studies have shown a correlation between dyslipidemia and coronary artery disease. 4,5 The Framingham study, conducted with about 5,000 residents of this community in Massachusetts, showed a increased risk of higher levels of LDL cholesterol and lower HDL. Once this correlation has been demonstrated, several studies have succeeded, confirming the hypothesis that it is possible to control cardiovascular events by normalizing cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%